EMDR in pediatric hospital setting: a case report of an adolescent with cancer - Ciappina, Sabrina; Roccia, Elvia; Concas, Deborah; Faretta, Elisa; Fernandez, Isabel; Quarello, Paola; Zucchetti, Giulia; Fagioli, Franca (Frontiers in Psychology, 2024)
Introduction: Childhood cancer is rare, but it is the most frequent serious event with a high risk of traumatization for children, adolescents, parents and siblings. EMDR is widely studied as clinical intervention that addressed cancer-related stressors among cancer adult population, but to our knowledge, no researches have been conducted among children and adolescent with cancer. Methods: The purpose of this case study is to describe for the first time the application of the EMDR protocol in a paediatric hospital setting with a 17-years-old Italian adolescent who received a diagnosis of leukemia. He accessed the psychological support service complaining of feelings of anxiety and general discomfort. EMDR protocol started after the diagnosis and ended after the usual eight phases. The Impact of Event Scale-Revised (IES-R) was used to assess stress disorders symptoms as outcome at the baseline (before the First Phase) and at the end of the EMDR protocol (after the Eight Phase). Results: By using EMDR protocol the patient reported a decrease of emotional activation after a few EMDR sessions. Conclusion: EMDR protocol may be effective for paediatric cancer patients in treating stress disorders symptoms and it can be proposed immediately after diagnosis as a standard care also in paediatric hospital setting.